Exploring intersectionality and HIV stigma in persons receiving HIV care in nurse-led public clinics in Durban, South Africa - Dudu G. Sokhela; Penelope M. Orton; Kathleen M. Nokes; William E. Samuels (Elsevier, 2023)
Background: Although stigma associated with South African people living with HIV has declined since the 1980s when HIV/AIDS was first identified, it still persists. Stigma is associated with poor health outcomes and avoidance of interactions with healthcare systems. The HIV stigma framework distinguishes three HIV-related self-stigma mechanisms. Aims: The aims of this study were to explore intersectionality between HIV-stigma mechanisms and selected sociodemographic as well as HIV factors, and interrelationships between three HIV-related self-stigma mechanisms. Setting and method: This study was a secondary analysis of data collected from a cross-sectional sample of people receiving HIV-related primary health care at different municipal clinics in Durban, South Africa (N = 100). Results: The average participant was Black African, female, unemployed, with a monthly income below R2 500, most had completed primary school. No sociodemographic or HIV-related factors were significantly related to total or subscale HIV stigma scores. Respondents reported experiencing (enacted) no stigmatization, did not expect to experience (anticipated) much stigmatization from their social interactions with family, community, healthcareworkers, and reported no strong stigmatizing beliefs about themselves (internalized). Conclusion: Intersectionality did not identify any particular socio-demographic or HIV-related factor associated with greater HIV stigma. Participants reported low HIV stigma arising from interactions with healthcare and social service providers or families. Although no socio-demographic or HIV-related factors were significantly associated with HIV stigma mechanisms in this relatively homogeneous sample, being marginalized can nevertheless result from living with other differences compared to societal norms and result in particular vulnerability when living with HIV/AIDS.